Виконання завдань з аудиту елементів та статей фінансової звітності як окремих об’єктів: вимоги та рекомендації Міжнародних стандартів аудиту - Роєва, О. С.; Roieva, О. (ЦНТУ, 2018)
У статті систематизовано вимоги Міжнародних стандартів аудиту в контексті виконання завдань з аудиту окремих фінансових звітів, окремих елементів, рахунків або статей фінансового звіту задля обґрунтування напрямів розвитку організаційного та методичного забезпечення таких завдань. Уточнена класифікація аудиторських послуг з метою чіткого їх виокремлення в складі завдань з аудиту. Запропонована їх додаткова деталізація. Обґрунтовано, що організаційні етапи та методика виконання таких завдань мають регламентувати відносини із управлінським персоналом і включати всі специфічні етапи, які вимагаються в процесі проведення аудиту всієї фінансової звітності, зокрема, розгляд шахрайства, законодавчих та нормативних актів, операцій та відносин із пов’язаними особами, облікових оцінок, подальших подій, іншої інформації, безперервності діяльності тощо. Selecting one object should simplify the auditor's work, since there is an opportunity to concentrate only on a narrow circle of operations, processes, etc. But on the other hand, the orientation of the International Standards on Auditing on regulating issues related to the audit engagements of the audit of entity’s complete set of financial statements, causes problems in their practical application in the process of conducting audits of certain articles, accounts, elements, items of financial statements. The purpose of this study is to systematize the requirements and recommendations of the International Standards of Auditing (ISA), in particular ISA 805 "Special Considerations - Audits of Single Financial Statements and Specific Elements, Accounts or Items of a Financial Statement", in the context of conducting of audits of single financial statements, items, accounts or articles of the financial statements in order to elaborate the directions of the development of organizational and methodological support for such engagements. It is substantiated that in spite of the existence of various audit classifications, the classification of audit services needs to be clarified in order to clearly distinguish the engagements of audit of single financial statement, accounts, articles and elements of financial statements. Their additional detailing into individual and integrated engagements, individual and complex engagements are offered ets.
Conducting the Engagements of Audit of Specific Elements and Items of a Financial Statement as a Separate Objects: Requirements and Recommendations of International Standards on Auditing
Keywords: аудиторські послуги; міжнародні стандарти аудиту; завдання з аудиту; окремий фінансовий звіт; елемент фінансового звіту; стаття фінансового звіту; рахунки фінансового звіту; audit services; International Standards on Auditing; audit engagement; single financial statements; element of a financial statement; item of a financial statement; account of a financial statement